SOSIALISASI MEMBANGUN KEJAYAAN MARITIM UNTUK PULIH LEBIH CEPAT, BANGKIT LEBIH KUAT AGAR LAUT BERSIH, RAKYAT SEJAHTERA BERSAMA LANAL BANJARMASIN DALAM GERAKAN NASIONALLAUT BERSIH TAHUN 2022 - Andri Ali Wardhana; Akhmad Syahbudin; Juhrani; Hadiansyah (BALANTING Jurnal Pengabdian kepada Masyarakat, 2023)
AbstractSocialization is a process of planting or transferring habits, or values and rules from one generation to another in agroup orsociety.As for the purpose of community service activities with Lanal Banjarmasin, lecturers and cadets of the BanjarmasinArchipelago Maritime Academy and children from the 10 Tabunio State Elementary School, of course, to motivate andprovide provisions for the surrounding environment that it is important to maintain cleanliness and immediately move toclean action in creating a prosperous life for the community. everything, and of course there is a collaboration built from mutualcooperation when cleaning the coastal environment to make it more beautiful and attractive.The conclusion is in the community service activity entitled socialization to build maritime glory to recover faster, risestrongerso that the sea is clean, the people prosper together with the Banjarmasin lanal in the national clean sea movement in2022.Keywords: Socialization, Maritime, Sea